Examining the Social and Cultural Implications of Philippine Folk Dance to College of Arts and Sciences (Cas) Students in One State University in the Philippines - Aquino, John Michael D. (Journal of Urban Culture Research, 2025)
The researcher aims to examine the social and cultural implications of Philippine Folk Dance to students in particular to their perceptions, attitudes, and how it affects the identity of the Filipinos. This study employed a phenomenological research design and purposive sampling in choosing the participant based on the given criteria. Semi-structured interviews was utilized and employed validated interview guide from the field expert and pilot testing. Thematic analysis was used in analyzing the data. The results revealed that the perception of the students profound admiration for the meaning, purpose, and beauty of traditional dances. Also emphasized are the value of cultural heritage preservation and the contribution of folk dancing to the development of Filipino pride, patriotism, and a feeling of identity. Additionally, Strong feelings of appreciation, pride, uniqueness, expressions, cultural ties, and engagement for their personal development. Moreover, folk dance has a significant effect on students' social and cultural identities.